2022
DOI: 10.1101/2022.01.31.478436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the possible role of hybridization in the evolution of photosynthetic pathways in Flaveria (Asteraceae), the prime model of C4 photosynthesis evolution

Abstract: Flaveria (Asteraceae) is the prime model for the study of C4 photosynthesis evolution and seems to support a stepwise acquisition of the pathway through C3-C4 intermediate phenotypes, still existing in Flaveria today. Molecular phylogenies of Flaveria based on concatenated data matrices are currently used to reconstruct the complex sequence of trait shifts during C4 evolution. To assess the possible role of hybridization in C4 evolution in Flaveria, we re-analyzed transcriptome data of 17 Flaveria species to i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 94 publications
2
8
0
Order By: Relevance
“…or antecedent traits from a parental lineage giving them an adaptive advantage that might have influenced their photosynthesis pathway, e.g., adaptations in photosynthesis or photorespiration associated enzymes or Kranz-cells. This is in line with recent findings in the genus Flaveria (Morales-Briones and Kadereit, 2022) where ancient hybridization was found to be a step towards C4 evolution and likely promoted the rapid acquisition of C4 traits. We also found hybridization events in the two clades in the other networks with similar parental lineages, supporting the evidence that these lineages were involved in hybridization events.…”
Section: Pepc Activity Has Little or No Correlation With γ Values Or ...supporting
confidence: 92%
See 2 more Smart Citations
“…or antecedent traits from a parental lineage giving them an adaptive advantage that might have influenced their photosynthesis pathway, e.g., adaptations in photosynthesis or photorespiration associated enzymes or Kranz-cells. This is in line with recent findings in the genus Flaveria (Morales-Briones and Kadereit, 2022) where ancient hybridization was found to be a step towards C4 evolution and likely promoted the rapid acquisition of C4 traits. We also found hybridization events in the two clades in the other networks with similar parental lineages, supporting the evidence that these lineages were involved in hybridization events.…”
Section: Pepc Activity Has Little or No Correlation With γ Values Or ...supporting
confidence: 92%
“…For a few examples, it has been suggested that this might also occur in nature (Dunning et al, 2017) which could mean an immediate adaptive advantage of the hybrid lineage in more stressful environments. A phylogenomic study of Flaveria revealed a major role of hybridization and transgressive segregation in C 4 evolution (Morales-Briones and Kadereit, 2022). In this study we aimed to infer the phylogenetic origin of C 3 -C 4 intermediacy of the Salsola divaricata agg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a few examples, it has been suggested that this might also occur in nature (Dunning et al ., 2017); that could mean an immediate adaptive advantage of the hybrid lineage in more stressful environments. A phylogenomic study of Flaveria revealed a major role of hybridisation and transgressive segregation in C 4 evolution (Morales‐Briones & Kadereit, 2022). In this study we aimed to infer the phylogenetic origin of the C 3 –C 4 intermediacy of the Salsola divaricata agg.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the possibility of a hybrid origin of a C 3 –C 4 intermediate lineage, detailed phylogenomic studies are needed. For example, evidence of recent and ancient events of reticulate evolution in a phylogenomic study of Flaveria revealed a potential major role of hybridisation in the evolution of C 4 photosynthesis in that genus (Morales‐Briones & Kadereit, 2022).…”
Section: Introductionmentioning
confidence: 99%